Da’wah Communication and the Hijrah Youth Movement: Islamic Identity and Social Change in Bandung - Yusuf, Yogi Muhammad (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study aims to examine how da'wah communication plays a role in shaping social change through the lifestyle of "hijrah" youth in Bandung City. The hijrah phenomenon, which has grown among urban youth, not only represents a resurgence of religiosity but also signifies a transformation in values, behavior, and social identity influenced by modern da'wah, especially through digital media. This research employs a qualitative approach using a case study method on several hijrah communities in Bandung, such as Pemuda Hijrah (Shift) and Shab Alqo. Data were collected through in-depth interviews, participatory observation, and documentation of digital da'wah activities. The results show that the hijrah movement among the younger generation in Bandung, particularly through communities like Pemuda Hijrah (Shift) and Shab Alqo, has had a significant impact on positive social change. This change is evident in the increased participation of youth in religious activities, a shift toward a more Islamic lifestyle, and the effective and interactive use of social media as a means of da'wah. Young people involved in hijrah communities tend to avoid promiscuity, be more selective in their entertainment consumption, and actively engage in religious studies, social activities, and the production of digital da'wah content. Moreover, these communities serve as platforms for religious identity expression, strengthen social networks based on Islamic values, and contribute to building a collective awareness to live more meaningful and spiritually and socially responsible lives.